It’s a match! – Building relationships between corporates and start-ups throughout Corporate Accelerators - Nesner, Tobias; Eismann, Tobias; Voigt, Kai-Ingo (Journal of Technology and Innovation Management, 2020)
A Corporate Accelerator (CA) is increasingly being considered as a bridge between established companies and start-ups. However, there is still little known about objectives and benefits of establishing CAs. Therefore, the aim of this study is to investigate both objectives and benefits of organizations implementing CAs. Moreover, we aim to shed further light on how those CAs are implemented in organizational structure and executed in corporate practice. We deliver findings based on data from five different cases in the German market. Using a multi case study approach, we find that CAs serve as so-called resource matchmakers between established companies and start-ups. Additionally, we propose that CAs trigger the organizational learning process. Therefore, we contribute to a better understanding of CAs, because prior research on this topic is limited. We discuss these findings in the light of prior research and with regard to management practice. Based on the limitations of our study, we provide avenues for further research.<br
Keywords: corporate accelerator; start-up collaboration; corporate entrepreneurship; organizational learning